Impact of post-Chernobyl radiation on flow cytometry parameters of human sperm - Nykolaichuk, Roksolana; Toporcerová, Silvia; Berbets, Andrii (Central European Journal of Public Health, 2022)
OBJECTIVE: The aim of this study was to analyse the long-term radiation effects on human sperm. METHODS: In total, 104 samples of male donors from 2 regions of Ukraine were tested. Group 1 consisted of 32 donors from the Ivano-Frankivsk region, group 2 included 72 volunteers from the Zhytomyr region. The average age of donors in both groups was 35 ± 6 years (range 24-49). To assess the level of apoptosis, membrane mitochondrial potential, concentration of reactive oxygen species, and ploidy of sperm, flow cytometry was performed. RESULTS: The individual equivalent dose of group 1 was < 0.4 mSv and of group 2 ≥ 0.4 mSv. Live spermatozoa with signs of apoptosis were significantly higher (p < 0.05) in group 2 in comparison to group 1 (15.6% and 11.2%, respectively). Spermatozoa without violating integrity were 73.2% in group 1 and approximately 16% higher than the indices of group 2. The percentage of dead necrotic spermatozoa was twice as high in men with a predicted equivalent dose of ≥ 0.4 mSv than in comparison group. A higher percentage of spermatozoa with low mitochondrial membrane potential, di- and tetraploid was found in group 2. CONCLUSIONS: An equivalent individual dose of ≥ 0.4 mSv can cause a decrease in mitochondrial potential, an increase in the production of spermatozoa with pathological ploidy, as well as to provoke increasing apoptosis in cells.
Keywords: Reactive Oxygen Species; dospělí; Semen; lidé středního věku; Flow Cytometry; průtoková cytometrie; mužské pohlaví; mladý dospělý; černobylská havárie; Chernobyl Nuclear Accident; reaktivní formy kyslíku; spermie; lidé; Middle Aged; Humans; sperma; Male; Young Adult; Adult; Spermatozoa